Analisis Paritas Daya Beli Kurs Rupiah terhadap Dolar Amerika Serikat Periode September 1997-Desember 2007 dengan Menggunakan Metode Error Correction: Model - AGUSTIN, GRISVIA (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang (FE UM), 2009)
Purchasing Power Parity themy is the one of exchange rate determination theory that commonly been tested its validity. This theory explains relationship among relative il·!flation rate with international currencv exchange rate. This 1·esearch uses en·or correclion model to test the validity of theory on rupiah exchange rate to American dollm· on the .floming exchange rate system. Data to be analyzed are monthly data from September 1997 to December 2007. Analysis result proves the validity if PPP theory in Indonesia. It is urging to maintain the price stability that re,flects inflation. The difference of price level can exacerbate exchange rate in the short term as well as in the long term.